Natural correction of hyperuricemia, not by allopurinol, could slow down the progression of renal disease in the patient with chronic kidney disease stage 3 - Kyung Sun Park; Jai Won Chang (The Korean Society of Nephrology, 2012)
Correction of hyperuricemia can slow down the progression of renal disease in animal study. However, there is limited data regarding the effect of lowering serum uric acid in patients with hyperuricemic chronic kidney disease (CKD) stage 3 (estimated GFR [eGFR] 30-60 mL/min). Methods: We retrospectively investigated 100 patients (age 56.1±9.9 years, M:F=79:21) with hyperuricemia (serum uric acid 7.9±0.9 mg/dL) and CKD stage 3 (eGFR 52.0±7.0 mL/min) 10 years ago. First, to evaluate the effect of allopurinol on the progression of renal disease, 23 patients who have taken allopurinol were compared with the randomly selected 23 patients according to the level of serum uric acid and eGFR as a control group among the other 77 patients who have never received allopurinol. Second, to clarify the effect of lowering serum uric acid by diet on renal disease progression, these 77 patients were divided into 2 groups by decreased amount of serum uric acid during 10 years and compared each other (group 1>1.0 mg/dL vs. group 2 <1.0 mg/dL). Results: First, although serum uric acid levels were significantly decreased (8.5±1.0 to 6.6±1.2 mg/dL, p<0.001) in subjects treated with allopurinol, the change of eGFR was not significant (48.8±8.6 to 44.5±18.5 mL/min, p=0.230). In control group, serum uric acid was also decreased (8.2±1.0 to 7.3±1.6 mg/dL, p=0.025) but eGFR did not change significantly (49.0±8.7 to 50.3±20.2 mL/min, p=0.726). Second, eGFR increased significantly (54.0±6.0 to 63.1±18.0 mL/min, p=0.002) in the group 1 whereas eGFR decreased (51.9±6.4 to 46.1±15.6 mL/min, p=0.008) in the group 2 after 10 years. In the multivariate linear regression analysis in the entire cohort (n=100), age (p=0.023), change of serum creatinine (p=0.001), and change of serum uric acid (p<0.001) were found to be significant factors that influence the change of eGFR during study period. Conclusions: We identified the protective effect of lowering serum uric acid against progression of renal disease in patients with CKD stage 3. However, allopurinol itself did not have such beneficial effect.